“Eldjoubaria”: A Constructive Critical Approach to Rules for Renewing the Teaching of French as a Foreign Language in Algeria - Djoubar, Ahmed; Ghilous, Salah (El Omda in Linguistics and Discourse Analysis, 2026)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:d5b1c4d3-357e-4700-8347-cbb529b42195-54" data-testid="conversation-turn-110" data-scroll-anchor="false" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="c511f568-a27a-4e70-b873-1c9c7ba0fb60" data-message-model-slug="gpt-5-3-mini" data-turn-start-message="true"> For several decades, the teaching of French as a foreign language (FLE) has been based on grammatical rules considered universal and immutable reference points. However, in the Maghreb context, and more specifically in Algeria, these rules often prove inadequate when confronted with learners’ cognitive, linguistic, and cultural realities. “Eldjoubaria,” developed from long field experience, proposes a critical and constructive reinterpretation of eight fundamental rules of French grammar in order to make them more accessible, logical, and coherent for FLE instruction. Rooted in a functional and humanistic perspective, this approach prioritizes meaning comprehension and communicative language use over mechanical memorization. The article presents the theoretical foundations of Eldjoubaria, outlines the eight revised rules through a process of simplification and clarification, and discusses their didactic implications for teacher training and textbook design. By redefining the place of key notions such as the verb, subject, theme, and the passé composé, this approach opens the way toward a more coherent, adapted, and contextualized linguistic pedagogy.